Regulated Ethylene Insensitivity through the Inducible Expression of the Arabidopsis etr1-1 Mutant Ethylene Receptor in Tomato(1)([OA]) - Gallie, Daniel R. (American Society of Plant Biologists, 2010)
Ethylene serves as an important hormone controlling several aspects of plant growth and development, including fruit ripening and leaf and petal senescence. Ethylene is perceived following its binding to membrane-localized receptors, resulting in their inactivation and the induction of ethylene responses. Five distinct types of receptors are expressed in Arabidopsis (Arabidopsis thaliana), and mutant receptors have been described that repress ethylene signaling in a dominant negative manner. One such mutant, ethylene resistant1-1 (etr1-1), results in a strong ethylene-insensitive phenotype in Arabidopsis. In this study, regulated expression of the Arabidopsis etr1-1 in tomato (Solanum lycopersicum) was achieved using an inducible promoter. In the absence of the inducer, transgenic seedlings remained sensitive to ethylene, but in its presence, a state of ethylene insensitivity was induced, resulting in the elongation of the hypocotyl and root in dark-grown seedlings in the presence of ethylene, a reduction or absence of an apical hook, and repression of ethylene-inducible E4 expression. The level of ethylene sensitivity could be controlled by the amount of inducer used, demonstrating a linear relationship between the degree of insensitivity and etr1-1 expression. Induction of etr1-1 expression also repressed the epinastic response to ethylene as well as delayed fruit ripening. Restoration of ethylene sensitivity was achieved following the cessation of the induction. These results demonstrate the ability to control ethylene responses temporally and in amount through the control of mutant receptor expression.